Head Trauma as a Precipitating Factor for Late-onset Leigh Syndrome: a Case Report - Ashrafi, Farzad; Pakdaman, Hossein; Arabahmadi, Mehran; Behnam, Behdad (Archives of Academic Emergency Medicine, 2017)
Leigh syndrome is a severe progressive neurodegenerative disorder with different clinical presentationsthat usually becomes apparent in the first year of life and rarely in late childhood and elderly years. It is causedby failure of mitochondrial respiratory chain and often results in regression of both mental and motor skills and might even lead to death. In some of the inherited neurodegenerative diseases like Alexander disease, head trauma is reported as a trigger for onset of the disease. We present a late onset Leigh syndrome in a 14-year-old girl whose symptoms were initiating following head trauma.